O papel do Conselho Municipal de Educação de Belo Horizonte na formulação de políticas para a educação infantil - Mayara Silva Cruz de Brito (2016)
This research investigates the role of the Municipal Council of Education of Belo Horizonte, in the formulation of public policies for early childhood education. The theoretical work reference is based on studies and concepts of Public Policy (Lasswell; Mainardes, Ball and Bowe; Lascoumes & Le Galès). The methodology adopted was the qualitative research, carried out from the data collection and analysis of documents, non-participant observation of CME meetings and semi-structured interviews with directors of different administrations (1998-2015). The study undertook a historical-conceptual discussion of the Board of Education seeking to explain its trajectory municipal education system from creation to the year 2015. Build up an overview of the development of early childhood education, deepening issues service history in the city of Belo Horizonte, in particular explaining the ways of regulating the formulation process of child educational services in the state capital. The work was guided, so the following questions: how is established the relationship from the CME / BH and its role in the trajectory of policies for early childhood education due to the very nature of this body in the municipal education system? If and how the organization of CME / BH was influenced by the early childhood education supply design in the city of Belo Horizonte? And what are the resulting actions of local childhood education setting and how these actions has shaped the performance of CME/BH as a body Municipal System of Education? As provisional findings work points out the following: a) the investigated CME has a strong presence in the formulation of public policies for early childhood education, achieved by the proposition of the resolutions that lay down the rules of the public offering and private in the city; b) the great demand for work received by CME in relation to institutions operating permit have occupied much of the body's agenda and emptied the deliberative and decision-making capacity by printing it a notarial and bureaucratized character within the system far short of its potential. The research shows the centrality of early childhood education in the developed activities, with emphasis on the role of early childhood education Technical Chamber, beyond the body's ability to enable more democratic experiences, with the participation of sectors of society and fostering other areas of discussion as Municipal Conference of Education. However, there was also that the body has moved to effect more like notarial instrument, which confirms the understanding that the decisions of educational policies are being made in other arenas, probably in the executive, the Department of Education.